Histopathology of inflammatory bowel disease — Position statement of the Pathologists of the Italian Group for the Study of Inflammatory Bowel Disease (IG-IBD) and Italian Group of Gastrointestinal Pathologists (GIPAD-SIAPEC). Issue 3 (March 2020) - Villanacci, Vincenzo; Reggiani-Bonetti, Luca; Caprioli, Flavio; Saragoni, Luca; Salviato, Tiziana; Mescoli, Claudia; Canavese, Gabriella; Manenti, Stefania; Spada, Elisabetta; Baron, Luigi; Leoncini, Giuseppe; Cadei, Moris; et al.
Abstract: Diagnosis of the inflammatory bowel diseases ulcerative colitis (UC) and Crohn's disease (CD) relies mainly on the histopathological examination of endoscopic biopsies of the gastrointestinal tract. To facilitate the accurate diagnosis of these two conditions, this paper addresses key issues on the: (A) gastrointestinal biopsy procedure, (B) histomorphological characteristics of UC and CD, and (C) diagnosis of dysplasia. The 13 statements presented here represent the consensus of two groups of Italian pathologists (IG-IBD and GIPAD).